Questioning the Judicial Service Commission’s role in curbing corruption amongst judicial officers - Ndiho, Sheila Wambui (Strathmore University, 2018)
Although it is true that corruption would negatively affect any organ, its effect on the judicial system cannot be overemphasized. This is due to the fact that the judiciary serves as a bulwark to the public against any encroachments on their rights and freedoms. As such, judicial independence is crucial to the functioning of any democracy. Historically, the biggest hindrance to judicial independence was the executive. This was in large part due to the degree of power that the repealed Constitution vested in the presidency. After the 2007 post election violence, it was clear that there was a desperate need for an independent judicial system that would promote the ideals of accountability and transparency. This study contends that there is a symbiotic link between judicial corruption, judicial independence and the concept of separation of powers. Indeed, the study sought to prove that the lack of judicial independence and the failure to maintain the appropriate balance of power between the judiciary, executive and legislature, acts as contributory factors leading to judicial corruption. To this end, the study relied on both primary and secondary sources of data in order to examine the history, nature, causes of and extent of judicial corruption in Kenya. Further, it examined reform initiatives implemented post 2010 as well as the history of the Judicial Service Commission (JSC) and the various challenges plaguing the institution to date. Through an analysis of the JSC’s powers of appointment, promotion, discipline and removal of judges, the study also reviewed international law with regards to the same. The study concluded that although the JSC’s mandates are at par with international best practices; that the JSC is at present not properly utilising the mandates accorded to it. Thus, the study recommends that certain incentives be introduced into the legal framework of the judiciary. These incentives inter alia include public awareness, amnesty and whistle blowing provisions and the strengthening of the judiciary fund.
Submitted in partial fulfillment of the requirements of the Bachelor of Laws Degree, Strathmore University Law School
Keywords: Civil Law Convention against Corruption (CILCC); Constitution of Kenya Review Commission (CKRC); Judicial Service Commission; Corruption